Erratum: Secondary Packaging Performance Assessment Based on Mechanical Damage Resistance Using Drop Testing and Forensic Packaging Methods at CV. Mubarokfood Cipta Delicia - Rheznandya Gaffi Rangga Saputra; Thalia Naziha (Agroindustrial Journal, 2026)
This Erratum relates to the following article:Saputra, R.G.R., Naziha, T., 2025. Secondary Packaging Performance Assessment Based on Mechanical Damage Resistance Using Drop Testing and Forensic Packaging Methods at CV. Mubarokfood Cipta Delicia. Agroindustrial Journal 12(1), 1–15. https://doi.org/10.22146/aij.v12i1.106078The publisher regrets that, due to a production error, the publication metadata on page 1 of the published PDF version of the article (DOI: 10.22146/aij.v12i1.106078) contained incorrect dates. The incorrect information appeared as: “Received: February 10, 2025; Accepted: June 05, 2024; Published: June 30, 2025”. The correct dates are: "Received: September 16, 2024; Accepted: June 05, 2025; Published: June 30, 2025".The editorial office regrets the error.